The factors that contribute to small and medium enterprises sustainability in Melaka / Ainatulhusna Mohd Rawi and Wan Nur Aqilah Zainudin - Mohd Rawi, Ainatulhusna; Zainudin, Wan Nur Aqilah (Faculty of Business Management, 2016)
This study was conduct among SMEs in Malacca to explore the most influential factors that contribute to sustainability. For this study, Independent Variables (IV); financial assistance, employees’ skills, business environments and technology capabilities were tested whether it influences another variable; SMEs sustainability to change. Besides that, this study is using Descriptive study, in which it emphasizes on collection of information and response that obtain directly from respondents in order to explain the actual situation faced by the respondents. The researchers are using cross-sectional studies because it involved the collection of data for once (one shot) or perhaps a period of days, weeks or months (specific time period). The researchers also distributed the questionnaires to the respondent that are available and freely to answer on the spot. For research sampling method, this research is using convenience sampling method because this type of sampling brought the meaning of the collection of information from the members of the population who are conveniently available and freely to provide the data and information, which is questionnaire are using as the instrument. The finding of this study shows that, all the Independent Variables (IV); financial assistance, employees’ skills, business environments and technology capabilities are significantly affecting the Dependent Variable (DV); SMEs sustainability. Therefore, the finding had shown that business environment is the most influential factors toward SMEs sustainability due to the beta value is the highest compared to the others independent variables.